The Invention of Territories and Hopes in the Era of Ecotourism in West Papua - Hatib Kadir (Jurnal Masyarakat dan Budaya, 2018)
This paper examines people from the bottom in responding new policies on nature conservation. They create their own territory based on the memories about their ancestors. The goal to preserve the nature and culture is even to be more integrated to the market exchanges. The research is conducted in Raja Ampat. A new kabupaten that defines their entire area as a protected place from natural exploitation. This approach is different from the previous treatment to nature of Raja Ampat. To earn cash means to destroy the forest. Rather, through ecotourism, the project expects to give a hope to the people. While preserving the nature, people even can get economic advantage. This paper is based on an ethnographic account. I hiked to the several important spots that also become the place of local people's ancestor. The aim was to get to know people's interaction with the nature and animals. Also, their social relations with other family clan and international NGO's.